MANAJEMEN IKLAN MEDIA CETAK MAKANAN RINGAN KRIPIK KUNYUK - Angga Pradipta Baskoro (JIKE: Jurnal Ilmu Komunikasi Efek, 2019)
The competition to find work in this competitive era of globalization while the jobs offered are limited and most of the company always looking for the experience in terms of the work at first to be able to work with good quality. Entrepreneurship is the one way to keep work and make a career for their lives in the future. One of the businesses that can easily recommend it to the public is business meals or similar culinary snacks. One type of snack food is macaroni that is one of the specialties in the shape of Italy is unique and very popular in the world, including in Indonesia. The macaroni into a business opportunities that promise because the type of snack food this much sought after consumers who love to try something different. This macaroni distributed in some areas. Keripik Kunyuk is a company that manufactures snack food while maintaining the quality of their products with unique flavour and it’s always innovates in order to draw attention to the new consumers and could hold consumers against loyalty to. One of his brand is Macaroni Nyuk. Therefore the author makes final project about Designing Print Media Advertising to improve Macaroni Nyuk Brand Awareness as a snack food that unique tastes and nutritious. The design of this print ad is a solution to solve the existing problems on the Macaroni Nyuk as well as to increase Brand Awareness in order to achieve the desired goal in advertising. Keywords: Communication management, Print Media Advertising, Brand Awareness